2003
DOI: 10.1074/jbc.m207198200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Studies of the Adipocyte-secreted Hormone Acrp30/Adiponectin

Abstract: Acrp30/adiponectin is an adipocyte-specific secretory protein that has recently been implicated as a mediator of systemic insulin sensitivity with liver and muscle as target organs. Acrp30 is found as two forms in serum, as a lower molecular weight trimer-dimer and a high molecular weight complex. Little is know about the regulation and significance of these Acrp30 complexes in serum and about the events that lead to the generation of the bioactive ligand. Here, we show that there is a profound sexual dimorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
893
6
43

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 980 publications
(963 citation statements)
references
References 38 publications
(48 reference statements)
21
893
6
43
Order By: Relevance
“…We only showed an inhibitory effect with gAdipo and our data are consistent with previous data showing that AdipoR1 is the main functional receptor for gAdipo and the effects of fAdipo are predominantly mediated via AdipoR2, this presumably explains why different effects have been attributed to the two forms of the hormone Kadowaki and Yamauchi, 2005). Some effects of adiponectin may be mediated by non-receptor mechanisms via the C1q-like domain (Kadowaki and Yamauchi, 2005) and as adiponectin has structural similarity to TNF- it has been suggested that receptor cross-reactivity could occur (Pajvani et al 2003). However our AdipoR1 RNA interference data suggest that the effects demonstrated here are mediated via the specific AdipoR1 receptor.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We only showed an inhibitory effect with gAdipo and our data are consistent with previous data showing that AdipoR1 is the main functional receptor for gAdipo and the effects of fAdipo are predominantly mediated via AdipoR2, this presumably explains why different effects have been attributed to the two forms of the hormone Kadowaki and Yamauchi, 2005). Some effects of adiponectin may be mediated by non-receptor mechanisms via the C1q-like domain (Kadowaki and Yamauchi, 2005) and as adiponectin has structural similarity to TNF- it has been suggested that receptor cross-reactivity could occur (Pajvani et al 2003). However our AdipoR1 RNA interference data suggest that the effects demonstrated here are mediated via the specific AdipoR1 receptor.…”
Section: Discussionsupporting
confidence: 92%
“…Our data suggest that the inhibition of leptininduced proliferation resides in the truncated globular adiponectin form; we have not specifically examined the effects of high-molecular weight adiponectin complexes. Native (and recombinant) full length adiponectin has a multimeric structure: polypeptides form homotrimers and these can link into hexamers and larger complexes (Pajvani et al 2003). In some systems the different high molecular weight forms have different biological actions Haugen and Drevon, 2007):…”
Section: Page 13 Of 28mentioning
confidence: 99%
“…Another potential limitation is the fact that adiponectin circulates in different forms with different states of oligomerization and glycosylation that may have functional consequences. 38,39 The implications of these are that there is need for standardization of assays used for the estimation of adiponectin. Furthermore, as the expression of the metabolic syndrome may be dependent on several factors that are linked to ethnicity, 40,41 it would also be necessary to establish the adiponectin cutoff level for the diagnosis of the metabolic syndrome for different populations.…”
Section: Discussionmentioning
confidence: 99%
“…With a total concentration of 5-20 nM, adiponectin exists in the circulation in the two aforementioned discrete oligomeric structures: the hexamer or low molecular weight form (LMW form) and the higher-order structure or high molecular weight form (HMW form). 28 A characteristic sexual dimorphism is found in mice and humans, with higher levels of the total adiponectin found in females. 29 In terms of complex distribution, the majority of adiponectin in males is present in the LMW form (while the HMW circulates in subnanomolar concentrations), whereas females display a more balanced distribution of the two complexes.…”
Section: Adipocyte-derived Secretory Factorsmentioning
confidence: 99%
“…29 In terms of complex distribution, the majority of adiponectin in males is present in the LMW form (while the HMW circulates in subnanomolar concentrations), whereas females display a more balanced distribution of the two complexes. 28 …”
Section: Adipocyte-derived Secretory Factorsmentioning
confidence: 99%